Corporate social responsibility communication : a case study of Oatly - Mendebaba, Alexandra (SLU/Dept. of Economics, 2019)
The concept of corporate social responsibility (CSR) offers a solution for businesses to identify their roles in society in order to maintain corporate legitimacy in cooperation with the communities they exist. Even though companies started to work with CSR as part of their business, CSR communication remained overlooked, and the literature is scattered around various disciplines. Therefore, this study intends to gain insight into the role of CSR communication between businesses and their multiple stakeholders. By connecting CSR with the corporate marketing philosophy, this study aims to identify key factors that promote CSR communication. At the same time, the study aspires to show the interlinkages between sustainability, corporate responsibility, and corporate marketing practices with attempts to better understand the communicative perspectives on CSR through a case from the food industry. The empirical analysis is structured in accordance with the pillars of corporate social responsibility: stakeholder theory, corporate marketing philosophy and the sharedunderstanding communication model. A qualitative method is applied to study the phenomenon of CSR communication through a single-case using Oatly AB as an empirical case. Besides, the focus group technique is included to explain how consumers perceive corporate communication intents. During the project, empirical data was collected from multiple sources, such as corporate sustainability report, code of conduct, semi-structured interview, available online materials and focus groups were organized. Findings of the study justify that communication has the value to foster sustainability and CSR in society through a dynamic interplay between the corporation and its constituencies. Proactive two-way dialogues, including and connecting diverse actors in decision-making, are key to produce, reproduce meaning and create reality. The empirical case illustrates that the combination of the political-normative and communicative aspects of CSR and constant negotiations have the potential to attain shared meanings and value. Moreover, openness and transparency perceived to be crucial factors in communication to promote sustainability in the food industry; complemented with authentic messages, consumers are likely to obtain clear meanings of communicational intents. However, the current marketing channels are not the most optimal; thus, new alternatives are needed to avoid communication gaps.